Statistical Methods in Forest Research - Nair, K. R. (Indian Forester, 1953)
The paper reviews the efforts made in the application of statistical methods to forest research in India during the last two decades and points out some of the common defects in experimental design and in the analysis of data of silvicultural experiments. The potentialities of factorial designs, incomplete blocks, etc., in the planning of silvicultural research are pointed out. The need for closest collaboration between research foresters and mathematical statisticians for exploring possibilities of replacing subjective free-hand curves by objective regression analysis in the evaluation of data for preparing yield and volume tables is stressed. Recent work on the technique of statistical sampling for timber surveys has been reviewed. Finally, some suggestions are given for raising statistical standards in forest research by international effort.